Retrospective evaluation of paired plasma creatinine and chloride concentrations following hetastarch administration in anesthetized dogs (2002–2015): 244 cases. Issue 3 (8th May 2019) - Zersen, Kristin M.; Mama, Khursheed; Mathis, Justin C.
Abstract: Objective: To evaluate changes in serum creatinine and chloride concentrations in anesthetized dogs that received 6% hydroxyethyl starch (HES) 670/0.7. Design: Retrospective case series, 2002–2015. Setting: University veterinary teaching hospital. Animals: Two hundred forty‐four client‐owned dogs undergoing general anesthesia that received an HES solution. Interventions: None. Measurements and Main Results: Medical records of dogs that received an HES solution (6%, 670/0.7) while under general anesthesia during the study period were reviewed. Information obtained from the medical record included patient signalment, reason for anesthesia or diagnosis, body weight, amount of HES solution administered, pre‐ and postanesthesia creatinine value, pre‐ and postanesthesia chloride value, and day interval between measurements. Corrected chloride values were used for all statistical analysis. Dogs received a median dose of 6.3 mL/kg hetastarch during anesthesia. Median preanesthesia creatinine and corrected chloride values were 79.5 μmol/L (0.9 mg/dL) (range 8.8–689.5 μmol/L [0.1–7.8 mg/dL]) and 111 mmol/L (111 mEq/L) (range 80–123 mmol/L [80–123 mg/dL]), respectively. Median postanesthesia creatinine was 57.4 μmol/L (0.65 mg/dL) (8.8–716 μmol/L [0.1–8.1 mg/dL]). Median postanesthesia corrected chloride was 115 mmol/L (115 mEq/L) (range 87.5–129.6 mmol/L [87.5–129.6 mEq/L]). Mann–Whitney test analysis revealed a significant decrease in creatinine (Δ Cr 17.7 μmol/L [0.2 mg/dL], P < 0.01) and a significant increase in corrected chloride (Δ Cl 4.1 mmol/L [4.1mEq/L], P < 0.01) between pre‐ and postanesthesia values. Conclusions: In a mixed population of hospitalized dogs undergoing general anesthesia that received a median dose of 6 mL/kg of HES, creatinine was lower and chloride was higher in the postanesthetic than in the preanesthetic period. The clinical significance of these changes and the role that HES administration played in them relative to concurrent therapies is unknown.